QUALITY MANAGEMENT SYSTEMS IN THE FOOD AND NUTRITION INDUSTRY: ENSURING SAFETY AND COMPLIANCE (International Journal of Food and Nutritional Sciences, 2021)
Abstract: Quality Management Systems (QMS) are essential in the food and nutrition industry, ensuring product safety, compliance with regulations, and maintaining high standards of quality. This paper examines the critical role of QMS in managing the complexities of food safety and quality control. It delves into the key components of effective QMS, including adherence to industry regulations such as the Food Safety Modernization Act (FSMA), ISO 22000, and Good Manufacturing Practices (GMP). The paper highlights the significance of documentation, risk management, employee training, and continuous improvement in maintaining product safety and regulatory compliance. It also addresses the challenges faced by organizations in implementing QMS, such as evolving regulations and resource constraints. Through case studies and industry examples, the paper illustrates successful practices and offers insights into overcoming common obstacles. It explores future trends and advancements in quality management, including technological innovations and global standards. By providing a comprehensive overview of QMS in the food and nutrition sector, this paper aims to offer valuable insights for organizations striving to enhance their quality management practices and ensure the safety and quality of their products.